Edukasi Cara Mengatasi Dismenorea dengan Akupresur di SMAIT Al-Azhar Kota Jambi - Julaecha, Julaecha; Nurbaiti, Nurbaiti; Wuryandari, Ajeng Galuh; Nurita, Suci Rahmani (Jurnal Abdimas Kesehatan (JAK), 2024)
Menstruation is a process of shedding the inner lining of the uterine wall that occurs periodically in women of childbearing age. During menstruation, most young women experience discomfort such as stomach cramps caused by uterine muscle contractions due to an increase in the hormone prostaglandin, pain during menstruation/dysmenorrhea can cause anxiety and disruption of activities. Pain can be treated with pharmacological and non-pharmacological therapies, one of which is acupressure on acupuncture points to relieve pain. This community service aims to provide knowledge and ways to overcome pain during menstruation with acupressure at the SP6 (Sayinjiao), Li4 (Hequ) and ST36 (Zusanli) acupuncture points. The method used is a question and answer lecture and showing the location of acupuncture points and practicing acupressure. Before being given education, the students' level of knowledge about menstruation and how to deal with menstrual disorders was first assessed, then the pain scale during menstruation was measured using the Numeric Rating Scale (NRS). The second stage is the delivery of material about menstruation and menstrual disorders (dysminorrhea) and acupressure to treat dysmenorrhea. As well as practicing acupressure, the third stage is a posttest to measure the students' knowledge after being given education and practicing acupressure. This community service will be carried out at SMAIT AL-Azhar Jambi City. with 75 respondents. The results of community service activities showed an increase in knowledge before being given education, an average of 37 people (49.3%) in the sufficient category (score 60-75), and after being given education, there was an increase in knowledge on average ≥ 76 or good knowledge of 45 people. (60%), female students can also practice acupressure to reduce pain during menstruation. This acupressure can be done independently, easily, anytime, anywhere without any side effects or costs